The state of the art : a chronicle of American poetry, 1988-2014 - Lehman, David, 1948- (Pittsburgh : University of Pittsburgh Press, 2015)
"This book collects all twenty-nine forewords from The Best American Poetry series. Beginning with a new introduction by David Lehman and a foreword by poet Denise Duhamel (guest editor for The Best American Poetry 2013), the collection conveys a sense of American poetry in the making, year by year, over the course of a quarter of a century"--
"The acclaimed annual, The Best American Poetry, is the most prestigious showcase of new poetry in the United States and Canada. Each year since the series began in 1988, David Lehman has contributed a foreword, and this has evolved into a sort of state-of-the-art address that surveys new developments and explores various matters facing poets and their readers today. This book collects all twenty-nine forewords (including the two written for the retrospective "Best of the Best" volumes for the tenth and twenty-fifth anniversaries.) Beginning with a new introduction by Lehman and a foreword by poet Denise Duhamel (guest editor for The Best American Poetry 2013), the collection conveys a sense of American poetry in the making, year by year, over the course of a quarter of a century"--
The Best of the Best American Poetry, 25th Anniversary Edition (2013). "Every time I read Pessoa I think"2013. It was his poetry that kept him going; 2014. In the antagonism between science and the humanities; Index of Names.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Poetics; American poetry -- 21st century -- History and criticism; American poetry -- 20th century -- History and criticism; Poétique.; Poésie américaine -- 20e siècle -- Histoire et critique; POETRY -- American -- General; LITERARY CRITICISM -- Poetry; American poetry; Poetics; 1900-2099; Criticism, interpretation, etc